Daya Hambat Ekstrak Daun Belimbing Wuluh (Averrhoa bilimbi L) Terhadap Bakteri Penyebab Jerawat (Propionibacterium acnes) - Nur Hasanah; Dede Rival Novian (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
One of the bacteria that causes acne is Propionibacterium acnes. Plants that are commonly used to treat zits are leaves of starfruit (Averrhoa bilimbi L), but their use is not so optimal, so a more practical formula needs to be developed. Face toner is one of the facial treatments that can help close the pores again. The purpose of this study was to determine the inhibitory power of the formulation of face toner preparation of starfruit leaf extract with a concentration of 1,25%, 2,5%, 5%, dan 10% towards the growth of Propionibacterium acnes bacteria. This study was an experimental laboratory using a disc diffusion method. Positive controls used were clindamycin a face toner of lime extract (commercial), while the negative controls used by sterile aqua dest. The test results of the formulation of face toner preparations for starfruit leaf extract have inhibitory effect on the bacteria Propionibacterium acnes, at concentration of 1,25% with an average diameter of 18,3 mm, a concentration of 2,5% with an average diameter of 18,6 mm, a concentration of 5% with an average diameter of 20,56 mm, and a concentration of 1,25% with an average diameter of 24,7 mm. Based on the results of the study, it can be concluded that the formulation of face toner extract of starfruit leaf extract has a zone of inhibition against Propionibacterium acnes with strong inhibitory response at concentrations (1.25% and 2.5%) and very strong at concentrations (5% and 10 %).Keyword : Inhibition, Starfruit leaf extract (Averrhoa bilimbi L), Disc Diffusion, Face toner, Propionibacterium acnes